Bentuk-Bentuk Etika Islam dan Rasionalisasinya - Nyayu Siti Zahrah (IAIN Bengkulu, 2021)
This study aims to determine the forms of ethics taught in Islam. where the forms of Islamic ethics and Western ethics have differences. In addition, this study also tries to see the rationalization aspect of ethical teachings in Islam. This research is a library research which will collect data related to the concept of Islamic ethics and its rationalization.The results of this study are the forms of Islamic ethics consisting of three main points, namely ethics to Allah, ethics to humans and ethics to the environment. In addition, the teachings of Islamic ethics also have rationalized values so that they can be proven through reason. So it can be said that ethical teachings in Islam are logical or make sense.